The effectiveness of scapular taping on pain and function in people with subacromial impingement syndrome: A systematic review. (1st October 2016) - McLaren, Cassandra; Colman, Zoe; Rix, Alana; Sullohern, Celia
Abstract : Background: Shoulder taping is commonly used to improve muscular dysfunction and glenohumeral alignment in patients with subacromial impingement syndrome (SIS). However, the implications of taping on the reduction of pain and increase in functional ability are yet to be established. Objectives: The objective of this systematic review is to synthesise the current available evidence on the effectiveness of shoulder taping on pain and function in patients with SIS. Data sources: Medline, AMED, EMBASE, and CINAHL were searched (April 2014) using keywords adapted for each database. Study selection: Three reviewers screened titles and abstracts for eligibility. Two reviewers independently selected relevant studies. Studies examining the effect of shoulder taping on pain and/or function in adults with SIS were reviewed. Data synthesis: Risk of bias was assessed using a 12-item quality scale. Qualitative synthesis was carried out using a 5-level rating system for best evidence synthesis. Results: Five studies were included ( n  = 98), three of high quality and two of low quality. One pilot randomised control trial (RCT) examined the effectiveness of rigid taping and found a short-term improvement in pain and function only. Three RCTs and one controlled clinical trial investigated the effect of kinesio taping and produced moderate evidence for short-term improvements in pain and function. Conclusions: There is limited, low-quality evidence for the effectiveness of rigid taping on pain and function in the short term. The application of kinesio taping using a variety of techniques has moderate evidence for reducing pain and improving function in the short term. Studies consistently found taping to be a useful adjunct to normal physiotherapy interventions in the short term. Further research is needed to compare types of tape and draw conclusions as to the long-term effects of shoulder taping.